Gravity waves amplify upper tropospheric dehydration by clouds. Issue 12 (22nd December 2015) - Schoeberl, Mark R.; Jensen, Eric J.; Woods, Sarah
Abstract: We use a 1‐D cloud model run using a prescribed temperature field to investigate the role of gravity waves in dehydration in the tropical tropopause layer (TTL). We find that gravity waves play an important role in the TTL dehydration process beyond just lowering the minimum temperature experienced by the air parcels. We show that the more rapid cooling in the presence of gravity waves significantly increases the abundance ice crystals. This increase in ice crystal concentration causes a more rapid depletion of vapor in excess of saturation, and the resultant cloud dehydration efficiency is increased. Using a spectrum of gravity waves, we generate ice particle statistics that are in good agreement with observations. We also find that the gravity waves increase cloudiness. Our results show that cloud physics and gravity wave temperature fluctuations cannot be neglected in simulating the TTL physics. In fact, it appears that short‐period waves may be an essential component of the TTL cloud dehydration process. Key Points: A cloud model is used to investigate upper tropospheric dehydration by waves The presence of gravity waves makes the dehydration process more efficient The increased efficiency is due to increased ice crystal formation by the waves